MODEL PEMBELAJARAN DEEP LEARNING DAN HUMAN-AI COLLABORATION DI KELAS SEKOLAH DASAR: TINJAUAN SISTEMATIS - Liyana Sunanto; Mahpudin (Jurnal Genta Mulia, 2026)
Deep learning and human-AI collaboration models have become a policy direction in Indonesianprimary education following the adoption of meaningful learning approaches within the KurikulumMerdeka in 2025-2026, in line with the global trend of integrating artificial intelligence (AI) intoprimary curricula. However, systematic studies examining the characteristics, effectiveness, andimplementation challenges of these two integrated approaches at the elementary school level remainlimited. This study aims to analyze and synthesize prior research findings regarding the design,implementation, and impact of deep learning models supported by human-AI collaboration inelementary classrooms, and to map research gaps relevant to the Indonesian context. This study employed a systematic literature review method following the PRISMA protocol, searching Scopus,ERIC, Google Scholar, Garuda, and SINTA databases using the keywords deep learning elementaryeducation, human-AI collaboration classroom, and AI literacy primary school, covering publicationsfrom 2020 to 2026. A total of 19 articles meeting the inclusion criteria were thematically analyzed andcoded into four theme categories. The coding results show that the characteristics of deep learning modelsdominated the findings (36.8%), followed by forms of teacher-AI collaboration (31.6%), impact onlearning outcomes and motivation (21.1%), and challenges and supporting factors for implementation(10.5%). Project-based learning and group collaboration supported by adaptive AI tools are mostconsistently associated with improved conceptual understanding, motivation, and digital literacyamong elementary students, although success depends heavily on teacher readiness, infrastructureavailability, and alignment with children's cognitive development stages. Key challenges includelimited teacher training, digital infrastructure gaps, and the absence of clear ethical guidelines for AIuse among elementary-aged students. This study recommends the development of co-design-basedteacher training models and contextual ethical frameworks as a foundation for AI integration policy inIndonesia's elementary curriculum